Persepsi Stakeholders Tentang Pengajaran Akuntansi Pemerintahan; Hambatan Dan Tantangan - Vita Fitria Sari; Mayar Afriyenti; Fefri Indra Arza (Universitas Negeri Padang, 2018)
This research aims to explore stakeholders’ perception towards government accounting subject education in public and private universities in Padang City as a part of regional management reforms. The purpose of this study to investigate stakeholders’ perception toward government accounting subject in the accounting curriculum; the level of lecturers’ teaching interest towards government accounting subject; the existence of teaching resources; and the suitability between users’ need and content of government accounting subject in higher education. Data was collected by questionnaire sent to stakeholders which consist of lecturers, students, and users and analyzed by using statistic descriptive. The results of this study found that government accounting subject already offer in accounting curriculum both bachelor and diploma degree on public and private university joined this study; but unfortunately government accounting subject only take 3 or 4 credit hours from total hours; less than 4% from total accounting curriculum. This study also found lack of lecturers teaching interest, also conventional learning method and resources for this subject. Fortunately, the content of government accounting subject in universities already suitable with users’ need. Some obtacles and challenges has been identified in this study can be condisered as recommendation in developing future government accounting education in university.